A Mixed-methods Study Examining Inhaler Carry and Use among Children at School. (2nd October 2020) - Volerman, Anna; Kim, Tae Yeon; Sridharan, Geetha; Toups, Madeleine; Hull, Ashley; Ignoffo, Stacy; Sharp, Lisa K.; Press, Valerie G.
Abstract: Objective: Asthma self-management depends partly on access to inhalers; for children, this includes independent inhaler carry and use at school ("self-carry"). Although laws and policies support self-carry, little is known about practices within schools. This study aimed to identify factors associated with inhaler self-carry among children and examine barriers and facilitators to self-carry. Methods: This mixed-methods observational study included child-parent dyads and nurses from four Chicago schools. Children and parents answered questions about asthma care and morbidity, confidence in self-carry skills, and facilitators and barriers to self-carry. Nurses reported asthma documentation on file and their confidence in children's self-carry skills. Analysis utilized logistic regression. Thematic analysis was performed for open-ended questions. Results: Of 65 children enrolled (mean = 10.66 years), 45 (69.2%) reported having quick-relief medication at school, primarily inhalers, and 35 (53.8%) reported self-carry. Inhaler self-carry was associated with controller medication use and parent confidence in child's self-carry skills. Children and parents identified several facilitators to self-carry: child's asthma knowledge, inhaler characteristics, and need for easy inhaler access. Barriers included child's limited understanding of asthma and inhalers, perception that inhaler is not needed, and limited inhaler access. Children also emphasized social relationships as facilitators and barriers, while parents described children's responsibility as a facilitator and inconsistent policy implementation as a barrier. Conclusions: Efforts to improve inhaler self-carry at school should focus on educating children about asthma and inhaler use, creating supportive environments for self-carry among peers and teachers, and fostering consistent implementation and communication about asthma policy among schools and families.